NILAI PERUSAHAAN YANG DIMEDIASI PROFITABILITAS (Studi Empiris Pada Perusahaan Property dan Real Estate di Bursa Efek Indonesia Tahun 2013-2016). - Mohklas Mohklas (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
The purpose of this study is to test, analyze the direct and indirect effects of Capital Structure and Company Growth on Firm Value through Profitability. So it can be seen which mediation path is the most dominant in influencing Company Value. In particular or managerial implementation is to provide input advice on the management of Property and Real Estate companies in making policies and decisions related to increasing company value. The variables in this study consisted of four variables where in the first stage the Capital Structure and Corporate Growth variables became independent variables while Profitability became the dependent variable. Then in the second stage of Capital Structure and Corporate Growth as independent variables, Profitability is an intervening variable, while the Corporate Value variable is the dependent variable. The population in this research is the Property and Real Estate companies listed on the Indonesia Stock Exchange from 2013 to 2016. The samples in this study were selected through purposive sampling, so that a sample of 80 companies was obtained. Data analysis method uses data analysis test; multiple linear regression and continued with path analysis. The results of this study are: Capital structure has a significant negative effect on profitability, company growth has a significant positive effect on profitability, capital structure has a significant positive effect on firm value, firm growth has no significant positive effect on firm value, and profitability has a significant positive effect on firm value. The capital structure has a significant positive effect on firm value, the magnitude of the direct effect is 0.226 and the indirect effect through profitability is -0.1844, the total effect is 0.1416. Company growth has no effect and no significant effect on firm value, the magnitude of direct influence is -0,088 and indirectly through profitability is -0,051, the total no influence is -0,139.